Near infra-red reflectance videography in the evaluation of retinal artery macroaneurysm pulsatility - Anmar Abdul-Rahman; William Morgan; Dao-Yi Yu (American Journal of Ophthalmology Case Reports, 2022)
Purpose: To describe pulsations of the retinal arteries detected in the course of evaluation of an exudative non-pulsatile retinal arterial macroaneurysm using near infra-red reflectance videography. Observations: A 68-year-old patient underwent slit lamp examination, color retinal imaging, optical coherence tomography, fluorescein videography, short wave-length and near infrared fundus autofluorescence of the left, and near infrared reflectance videography of both eyes. A 1309.3 × 955.1 μm exudative lesion with intraretinal hemorrhage and retinal edema secondary to a retinal arterial macroaneurysm was observed along the superior temporal arcade between the retinal artery and vein. Bilateral serpentine and expansile spontaneous retinal artery pulsations were detected along the retinal vascular tree and imaged using near infrared reflectance videography. Fluorescein video-angiography showed an irregular filling defect of the lesion with minimal angiographic leakage. Whereas pulsations of the retinal arteries were visualized, no pulsations of the retinal arterial macroaneurysm were detected with either dynamic imaging modality, therefore observation was recommended. Significant spontaneous lesion regression was observed at one month follow-up. Conclusionand Importance: Detection of spontaneous retinal artery pulsation and the assessment of exudative maculopathy due to an underlying retinal arterial macroaneurysm could be facilitated by near infrared reflectance videography. This imaging modality can aid in clinical decision-making where a non-pulsatile macroaneurysm would favor conservative management.